Incentive for information sharing through revenue-sharing contracts in a logistics service provider and customer relationship. (2018) - Elbert, Ralf; Tränkner, Cora; Özsucu, Özhan; Gleser, Michael
The purpose of this research is to evaluate the effect of revenue-sharing contracts in the setting of a logistics buyer-supplier relationship on the willingness to share information between the actors involved. As interests of the actors are aligned when using a revenue-sharing contract, the willingness for information sharing is expected to increase. This increase will lead to improvement of overall performance within the relationship. To measure the impact of the revenue-sharing contract on willingness for information sharing, a laboratory experiment is conducted. Basis of this experiment is a modified investment game, allowing for information sharing possibilities. The use of an experimental setup allows for a controlled environment and reproducibility when analysing the behaviour of the actors involved. To evaluate the data obtained from our laboratory experiment, non-parametric statistics are applied. The results of the experiment indicate a significant change in the subjects' behaviour when a revenue-sharing contract is in place. Results show an increase in willingness to share information when a revenue-sharing contract is introduced as well as increased overall profits. The results of the experiment indicate that revenue-sharing contracts have the potential to evoke the willingness for information sharing.